Comparison between modern electronic marketing and classic marketing (Review article) (The Peerian Journal, 2025)
Recent decades have witnessed radical transformations in the world of marketing, as e-marketing has emerged as a powerful alternative to traditional classical marketing. Classic marketing relies on traditional media such as television, radio, newspapers, and magazines, and is characterized by one-way communication and reaching a wide audience. On the other hand, e-marketing relies on digital platforms such as social media, email, and search engines, and is characterized by direct interaction with the audience, low cost, and ease of measuring performance. This study aims to compare modern e-marketing and classical marketing, focusing on the fundamental differences between them in terms of audience interaction, cost, measuring effectiveness, customization, and the means used. The study will also review the advantages and disadvantages of each, while providing practical examples from case studies of companies that have succeeded in using each approach. The study will conclude that choosing the appropriate marketing approach depends on the nature of the target audience, the available budget, and the marketing goals of companies